2013
DOI: 10.1088/0957-4484/24/33/335201
|View full text |Cite
|
Sign up to set email alerts
|

Conductance quantization in a Ag filament-based polymer resistive memory

Abstract: Resistive switching and conductance quantization are systematically studied in a Ag/poly(3-hexylthiophene):[6,6]-phenyl-C61-butyric acid methyl ester/indium-tin oxide sandwich structure. The observed bipolar switching behavior can be attributed to the formation and dissolution of Ag filaments during positive and negative voltage sweeps, respectively. More importantly, conductance quantization with both integer and half integer multiples of single atomic point contact can be realized by slowing down the voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 22 publications
4
79
0
Order By: Relevance
“…This picture [7] is based on the observation [12] that, for a sufficiently high write current, the ON-state conductance of Ag/GeS 2 cells tends to be an integer multiple of G 0 =2e 2 /h (Fig. 3), as observed earlier in gap-type "atomic switches" [14] and recently in many other types of gapless cells [15][16][17][18][19][20][21][22]. Quantization of the conductance implies Fig.…”
Section: Discussionmentioning
confidence: 91%
“…This picture [7] is based on the observation [12] that, for a sufficiently high write current, the ON-state conductance of Ag/GeS 2 cells tends to be an integer multiple of G 0 =2e 2 /h (Fig. 3), as observed earlier in gap-type "atomic switches" [14] and recently in many other types of gapless cells [15][16][17][18][19][20][21][22]. Quantization of the conductance implies Fig.…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, observation of quantized conductance discrete steps characterized by integer or half integer multiples of G 0 5 2e 2 /h has been reported in ECMs 8,[12][13][14][15][16][17][18] and VCMs. [19][20][21][22][23] While there is a few studies on the conductance quantization effect in TCMs, 14,24 we have reported that a conductive filament including a quantum point contact (QPC) can be formed in Pt/NiO/Pt RS cells.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Essentially, conductance quantization is seen during ballistic electron wave transmission through a constriction with a lateral dimension that is comparable to the Fermi wavelength of the electrons. 1 In the research field of RRAMs, conductance quantization means that the conductance (G) of a RRAM cell in the LRS can be expressed as G ¼ nG 0 (n ¼ 1, 2, 3, …), where G 0 ¼ 2e 2 /h % 77.5 lS (e is the electron charge and h is Planck's constant) refers to a single atomic point contact.…”
mentioning
confidence: 99%
“…Due to the absorption of impurities on or in the conducting filaments, half-integer quantized conductance values, i.e., G ¼ (n À 1/2)G 0 , are also frequently observed. 10,12 It is apparent that multilevel storage will be easily realized if these quantized conductance values can be well controlled. Up to now, conductance quantization has been reported only in several RRAM systems, which can be classified into two categories based on the switching mechanisms.…”
mentioning
confidence: 99%